Integration of STEM and Local Wisdom: Development of the Herbal STEMpreneur Model to Enhance 21st-Century Skills among Senior High School Students - Andika Kuncoro Widagdo; Nurul Farikhatir Rizkiyah; Aji Fajar Ramadhani; Lucia Tri Pangesthi; Ratna Palupi Nurfatimah; Raida Amelia Ifadah; Patni Patni (Universitas Negeri Semarang, 2025)
This study aims to develop and test the effectiveness of the STEMpreneur Herbal Model as a STEM-based learning innovation integrated with local wisdom through the use of herbal plants to improve students' 21st-century skills. Using a mixed-methods approach with an explanatory sequential design, the study involved 32 Grade XI students from SMA Negeri 1 Karas Magetan through six weeks of project-based learning. Quantitative data were collected through critical thinking tests, creativity questionnaires, collaboration, and entrepreneurial literacy, while qualitative data were obtained from observations and interviews. The results showed a significant increase in critical thinking (Cohen's d = 1.21), creativity (+36.7%), collaboration (+25%), and entrepreneurial literacy (+30%), with the first three variables being the main predictors of entrepreneurial literacy. Qualitatively, students showed high engagement, appreciation for local knowledge, and increased motivation to learn. The Herbal STEMpreneur model proved effective in fostering 21st-century competencies, strengthening the Pancasila Student Profile, and contextualising science in real life. Wider implementation is recommended through interdisciplinary teacher training, adaptation of a curriculum based on regional potential, and collaboration with MSMEs and universities to support the sustainability of relevant and character-building STEM education.